Sea and island economy development with environmental protection in Nha trang city, Khanh hoa province - Van Dung, Vo; Nhat Minh, Tran (Nexo Revista Científica, 2023)
Sea and island economic development associated with environmental protection is an issue of concern for research. In this article, we will focus on answering three questions: Why should marine and island economic development be associated with environmental protection?; What are the benefits of protecting the marine and island environment for economic development? Is it possible to protect the marine and island environment without economic development or develop an economy without protecting the environment? To answer those three questions, we clarify the reality of economic development associated with environmental protection in Nha Trang city, Khanh Hoa province, the result of the economic development of sea and islands for environmental protection and the effect of environmental protection to the development of sea and island economy.